2020
DOI: 10.3390/en13030661
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Diagnosis of Defect in GIS Based on X-ray Digital Imaging Technology

Abstract: For better application of X-ray digital imaging technology in defect detection in Gas Insulated Switchgear (GIS), it is essential to investigate the typical defect and establish the defect database, which has not been adequately performed in previous work. Systematic experimental research is also needed to accumulate data and experience. In this research, an experimental platform, including Computed Radiography (CR) imaging system and a GIS model, is built, and extensive tests of different kinds of typical def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Similar to electrical discharge and thermal induced decomposition, SF6 decomposes when exposed to x-ray irradiation. In certain applications, x-ray units are used in the vicinity of SF6insulated equipment for the purpose of equipment defect detection using digital imaging technology [46][47] [48]. Xray has been introduced as a defect detection technique due to its ability to penetrate and visually provide results for the internal status of GIS.…”
Section: Sf6 Decomposition By X-ray Irradiationmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to electrical discharge and thermal induced decomposition, SF6 decomposes when exposed to x-ray irradiation. In certain applications, x-ray units are used in the vicinity of SF6insulated equipment for the purpose of equipment defect detection using digital imaging technology [46][47] [48]. Xray has been introduced as a defect detection technique due to its ability to penetrate and visually provide results for the internal status of GIS.…”
Section: Sf6 Decomposition By X-ray Irradiationmentioning
confidence: 99%
“…This classification approach uses techniques such as the PD measurements, PD phase resolution (PRPD) pattern and X-ray irradiation to identify the types of defects in GIE. X-ray digital imaging technology was applied to detect various defects: metal and flaky particles, Loosened Metal Screws, and different adsorbent cover materials [46]. The investigation concluded that the technique for visually detecting defects in GIS was effective.…”
Section: A Non Dca Based Classificationmentioning
confidence: 99%
“…Recently, several scholars have introduced X‐ray digital radiography technology to realise visualisation results of the components inside GIS equipment [9]. X‐ray technology gets the advantages of non‐contact, high penetration, and non‐destructive inspection [10].…”
Section: Introductionmentioning
confidence: 99%
“…Conventional nondestructive testing methods are widely used but they have some limitations [5][6][7]. For example, visual testing can easily miss detection [8][9][10]; radiographic testing has radiation risk and its equipment cost is high [11]; magnetic particle testing and penetration testing can locate the defect position but cannot specifically display its shape; and eddy current detection and other signal detection technologies can not directly reflect the defect shape [12].…”
Section: Introductionmentioning
confidence: 99%